PENGARUH PERASAN UMBI AKAR LOBAK (Rhapanus sativus L) TERHADAP PENINGKATAN KADAR PROLAKTIN DALAM DARAH MENCIT (Mus musculus) BETINA - Mas Loegito; Paulus Liben; Thin Soedarti (The East Java Biological Society, 2006)
The objective of this research was to prove that the administration of radish tuber extract (Rhapanus sativus L) to female mice (Mus musculus) might increase blood prolactin level. This was an experimental research using complete randomized design by involving three treatment groups and three control group, each with five replications. Materials consisted of radish tuber extract and 30 female mice of 8 weeks old divided into 6 groups, i.e., control groups of C1, C2, and C3, and treatment groups of T1, T2, and T3. C1, C2, and C3 groups were given water of 1 × 0.5 cc/day per oral, 2 × 0.5 cc/day, and 3 × 0.5 cc/day respectively. Treatment groups of T1, T2, and T3 were given radish tuber extract of respectively 1 × 0.5 cc/day per oral, 2 × 0.5 cc/day, and 1 × 0.5 cc/day. Treatment was carried out for 21 days. Blood was subsequently taken from those rats for blood prolactin level. Data were analyzed using Anove test. If the results indicated significant difference of 95% (p = 0.05), the analysis was continued with LSD. The conclusions of this experiment is the administration of radish tuber extract per oral may result in the increase of blood prolactin level.